Maintaining Authenticity of AI-assisted Works for Indonesian and Philippines Creative Writing Learners: Students’ Experience and Reflection: Students’ experience and reflection - Khristianto Khristianto; Ana Mae M. Monteza; Ambhita Dhyaningrum; Ilham Rabbani (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The advance in artificial intelligence (AI) are significantly influencing various fields, including literature and creative writing. In Indonesia and the Philippines, AI is increasingly used to assist novice writers in creating fictional works. Employing a qualitative approach, the research utilizes data sources: fictional texts created by learners (high school and college students) using AI; the learners' perceptions of their creative process. The findings shows that the majority of submitted work was of good quality (65%), with 30% rated as "excellent." High-quality work contained little AI-generated content (maximum 12.3%), reflecting a strong personal contribution from the authors. Despite limited prior experience in narrative writing (87%), AI tools played a significant role in improving students' narrative skills, as evidenced by the assessed quality of their work. While nearly half of students found AI useful for improving expression (44%) and generating ideas (30%), most (86%) doubted its ability to make writing more enjoyable, and many (69%) expressed concerns about overreliance and a loss of originality. The findings highlight the importance of structured pedagogical guidance to help students leverage AI effectively while maintaining their unique voice and developing their narrative skills. The findings are expected to offer practical recommendations for educators, policymakers, and the writing community on ethically and effectively integrating AI in creative learning, particularly in Indonesia and Philippines.